HARMFUL RECIPROCAL RELATIONSHIP BETWEEN HUMAN AND NATURE PORTRAYED IN THE EPIC MOVIE - WIDIYANTI, DIYA SRI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Ecocriticism, Human and Nature, Environmental, Epic Movie Environmental problems become the trending topic in development of modern technology era nowadays. The environmental problems are studied specifically in ecocriticism. These problems are usually caused by unbalance relationship betweenhuman and nature. In this research, the researcher analyzes harmful reciprocal relationship between human and nature portrayed in the Epic movie.  The problem ofthe research is divided into two points; (1) The harmful reciprocal relationship between human and nature, (2) The impacts of the relationship between human andnature described in the Epic movie.This research uses qualitative method to analyze data because the data are in the form of utterances and figures taken from the movie. In addition, the researcher explains the result in the form of description rather than numeral. Hence, qualitativemethod is the most appropriate method to analyze Epic movie. Furthermore, Ecocriticism is used to analyze the movie.The result shows that humans can exploit nature as research object without any concern about the impacts. Nature is also exploited as medium to establish human’s power. Humans gain benefit from the relationship because they can improve their quality of life but nature becomes increasingly damaged. Moonhaven which is originally beautiful with balance ecosystem becomes unbalance and dry.The researcher suggests the next researchers to use Ecocriticsm theory in analyzing different movie like “The Lorax Movie” to show the impact of development of technology toward nature. This movie tells that humans create artificial natural object such as trees which are made of plastic. Moreover they must buy fresh oxygen to respire.